2017
DOI: 10.1007/978-3-319-39546-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Chronic Diseases of Consciousness: State of the Art in Neuromodulation for Persistent Vegetative State and Minimally Conscious State

Abstract: Chronic diseases of consciousness (CDC) can still be considered a challenging frontier for modern medicine, probably because of their not completely understood physiopathological mechanisms. Following encouraging evidence on cerebral hemodynamics, some authors have hypothesized a role for neuromodulation in the treatment of CDC patients. In the past 40 years, spinal cord stimulation (SCS) and deep brain stimulation (DBS) have been used experimentally for the treatment of patients in a severe altered state of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…SCS has been demonstrated as a valuable brain-intervention technique for rehabilitating DOC patients (Georgiopoulos et al, 2010; Mattogno et al, 2017; Yamamoto et al, 2017). But there was still few studies investigating the potential mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCS has been demonstrated as a valuable brain-intervention technique for rehabilitating DOC patients (Georgiopoulos et al, 2010; Mattogno et al, 2017; Yamamoto et al, 2017). But there was still few studies investigating the potential mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, spinal cord stimulation (SCS) has become a valuable brain-intervention technique for rehabilitating DOC patients because it is a less-invasive, simpler surgical procedure than deep-brain stimulation (Georgiopoulos et al, 2010; Mattogno et al, 2017). Studies have shown its efficacy in modulating the brains of DOC patients (Yamamoto et al, 2012, 2013, 2017), but the underlying mechanism of its effects on the cerebral cortex is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One could concern that the relatively small sample size limits the significance of multiple comparisons made (as the required sample size increases linearly with the logarithm of the number of comparisons made). However, the required sample size for detecting a between-group difference between TDCS after-effects using the typical conventions of 80% power, a two-tailed alpha of 0.05, and a putative metaplasticity effect size of approximately 0.40 (in keeping with the available literature data on TDCS in patients with DoC), [98][99][100][101][102][103][104][105] should be of at least 35 subjects, 106,107 which is satisfied by our sample. Further, the differences between the patients with DoC were statistically significant, as also shown by the effect size data indicating a big effect of TDCS on SICI, above all.…”
Section: Limitation and Conclusionmentioning
confidence: 52%
“…There has been extensive clinical and basic research into treatments for DOC treatments, including electrical nerve stimulation: in DOC this mainly involves median nerve electrical stimulation (MNES) [5][6][7], spinal cord electrical stimulation (SCS) [8][9][10], transcranial direct current stimulation (tDCS) [11][12][13], vagus nerve stimulation (VNS) [14,15], or deep brain stimulation (DBS) [16,17]. However, there is no unified DOC treatment guideline [18].…”
Section: Introductionmentioning
confidence: 99%